Laparoscopic left-sided hepatectomy for the treatment of hepatolithiasis: A comparative study with open approach. (April 2017) - Peng, Long; Xiao, Jian; Liu, Zhanying; Zhu, Jisheng; Wan, Renhua; Xiao, Weidong; Li, Yong
Abstract: Background: Hepatolithiasis is a prevalent disease in some regions of China. Left-sided hepatectomy is an effective treatment for left intrahepatic bile duct stones with irreversible disease, such as biliary strictures, severe parenchymal fibrosis or atrophy. However, the advantages of laparoscopic left-sided hepatectomy (LLH) over open approach (OLH) are still controversial. The aim of this study was to compare the clinical outcomes of LLH to those of OLH in the treatment of hepatolithiasis. Methods: Between January 2013 and October 2016, 75 consecutive patients with hepatolithiasis undergoing left-sided hepatectomy were enrolled in this study. The demographic, intraoperative, and postoperative data were retrospectively analyzed. Results: Among these 75 patients, 36 underwent LLH (LLH group) and 39 underwent OLH (OLH group). The LLH group exhibited a lower intraoperative blood loss (215.8 ± 75.8 vs 298.7 ± 158.9 mL, p  = 0.005), intraoperative transfusion (5.6% vs 23.1%, p  = 0.032), overall complication rate (13.9% vs 35.9%, p  = 0.029), and shorter recovery of bowel movement (2.3 ± 0.8 vs 3.0 ± 1.0 d, p  = 0.004), time of off-bed activities (3.2 ± 1.1 vs 5.8 ± 1.4 d, p  < 0.001) and postoperative hospital stay (7.7 ± 2.2 vs 10.9 ± 3.3 d, p  < 0.001) compared to the OLH group. Similar results were also observed in left lateral sectionectomy and hemihepatectomy subgroups. There was no significant difference in the operative time, initial stone clearance rate, final stone clearance rate, stone recurrence rate and overall cost (All p  > 0.05). No perioperative mortality was observed. The conversion rate was 5.6%. Conclusion: LLH is a safe and effective treatment for selected patients with hepatolithiasis, with an advantage over OLH in the field of intraoperative blood loss, intraoperative transfusion, overall complication and postoperative recovery. Highlights: LLH is a safe and effective treatment for hepatolithiasis and exhibits advantages over OLH in some fields. The conversion rate was 5.6% for LLH. No obvious differences showed in operative time, initial/final stone clearance rate and stone recurrence rate in both groups.